2020
DOI: 10.1101/2020.10.29.360081
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Infant functional connectivity fingerprints predict long-term language and pre-literacy outcomes

Abstract: Functional connectivity analyses can delineate brain organization in infancy, enabling the characterization of early brain characteristics associated with subsequent behavioral outcomes. Previous studies have identified specific functional networks of infant brains that underlie cognitive abilities and pathophysiology subsequently observed in toddlers. However, it is unknown whether and how functional networks emerging in infancy contribute to the development of higher-order complex functions of language and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 106 publications
(115 reference statements)
3
1
0
Order By: Relevance
“…There were no reliable increases in within-vs. between-network FC cross-sectionally and longitudinally, which suggests that specificity of connections are more static than neural specificity, at least for the domain of language. This supports previous work testing the connectivity-fingerprints hypothesis, where connectivity precedes and perhaps drives the functional organization and specificity of cortex (Hannagan et al, 2015;Li et al, 2020;Saygin et al, 2016;Yu et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…There were no reliable increases in within-vs. between-network FC cross-sectionally and longitudinally, which suggests that specificity of connections are more static than neural specificity, at least for the domain of language. This supports previous work testing the connectivity-fingerprints hypothesis, where connectivity precedes and perhaps drives the functional organization and specificity of cortex (Hannagan et al, 2015;Li et al, 2020;Saygin et al, 2016;Yu et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…Finally, when examining the connectivity within and between the language and MD networks, we found no reliable increases in within- vs. between-network FC cross-sectionally and longitudinally. This suggests that specificity of connections may be more static than neural specialization, at least for the domain of language, supporting previous work testing the connectivity-fingerprints hypothesis, where connectivity precedes and perhaps drives the functional organization and specificity of cortex (Hannagan et al, 2015; Li et al, 2020; Saygin et al, 2016; Yu et al, 2020). Prior longitudinal work has suggested that changes in within-network connectivity is associated with changes in language performance, as opposed to age (Xiao, Brauer, et al, 2016; Xiao, Friederici, et al, 2016); however, we could not test that hypothesis with our data.…”
Section: Discussionsupporting
confidence: 82%
“…Finally, when examining the connectivity within and between the language and MD networks, we found no reliable increases in within‐ versus between‐network FC cross‐sectionally and longitudinally. This suggests that specificity of connections may be more static than neural specialization, at least for the domain of language, supporting previous work testing the connectivity‐fingerprints hypothesis, where connectivity precedes and perhaps drives the functional organization and specificity of cortex (Hannagan et al, 2015 ; Li et al, 2020 ; Saygin et al, 2016 ; Yu et al, 2020 ). Prior longitudinal work has suggested that changes in within‐network connectivity is associated with changes in language performance, as opposed to age (Xiao, Brauer, et al, 2016 ; Xiao, Friederici, et al, 2016 ); however, we could not test that hypothesis with our data.…”
Section: Discussionsupporting
confidence: 80%
“…Second, the networks we have identified are putative functional networks with nomenclature based on topography or overlap with adult networks. Longitudinal studies could identify the relationship between these networks and various mental functions as they manifest, e.g., measured via behavioral measures, such as language and literary skills (Yu et al, 2020), and/or neural measures, such as task-based fMRI (Saygin et al, 2016). Third, the genetic analyses are based on adult tissue samples, and are strictly exploratory.…”
Section: Discussionmentioning
confidence: 99%